Factors affecting seafarers’ fatigue: a scoping review - Ma, Mingfei; Liao, Ruolin (Frontiers in Public Health, 2025)
BackgroundNowadays, many maritime accidents occur due to the fatigue of seafarers. With the rapid development of the economy and society, the factors affecting seafarers’ fatigue are also changing. At present, there is a lack of systematic articles that examine the factors influencing seafarers’ fatigue over the past decade. This review aims to explore the various factors related to seafarers’ fatigue through a scoping review, to identify effective approaches to addressing the fatigue issues faced by seafarers.MethodsStudies were searched on PubMed, Science Direct. Academic search complete using EBSCOhost databases, Springer Nature Link, and Web of Science in May 2025. This scoping review was conducted based on the framework of Arksey and O’Malley and the Preferred Reporting items for Scoping Reviews flow diagram. The inclusion criteria were studies that determined the relationship between factors relevant to seafarers’ fatigue, including physical conditions and mental issues, etc. Data were narratively summarized and reported.ResultsEighteen articles were included in this review, while 18 major findings were clarified. Firstly, fatigue among seafarers has been frequently discussed over the past decade. Secondly, the factors influencing seafarers’ fatigue can be categorized into three aspects: the seafarer’s own factors, the working environment factors, and the management factors. The seafarer’s own factors include physiological factors, psychological factors, and sociological factors. The working environment factors include safety climate, external support, work demands, work mode, and ship conditions. The management factors include those at the ship, system, technology, industry, and national regulations levels.ConclusionAt the individual level, focus on the accumulation of psychological capital and enhancing work autonomy can alleviate fatigue. More solutions need to be implemented at the organizational level, including providing a better sleep environment, providing more external support, flexibly handling work demands and work patterns, and improving technology and management measures.